UPAYA MENINGKATKAN HASIL BELAJAR BOLA VOLI MELALUI MODIFIKASI BOLA VOLI MINI PADA SISWA KELAS IV DI SD NEGERI 06 BATANG GASAN - Ernalita Ernalita (JURNAL MANAJEMEN PENDIDIKAN, 2017)
Based on the results of the fourth grade students of SDN 06 Batang Gasan subjects sub Volleyball PE found that the learning outcomes of students in the subjects of PE sub Volleyball is still very low. The average student learning outcomes are still under KKM. The purpose of this study is to describe and obtain information about efforts to improve student learning outcomes in subjects Penjaskes sub Volleyball Volleyball Through Modified Mini in fourth grade N 06 Batang Gasan Padang Pariaman district.This research is a class act. The procedure in this research include planning, action, observation and reflection. The study consisted of two cycles of the four meetings. Subjects consisted of 15 people learners in grade IV SDN 06 Batang Gasan. Data were collected by using observation sheet and daily tests. Data were analyzed using percentages.Based on the results of research and discussion that has been raised, it can be concluded that the Volleyball Mini can improve student learning outcomes in subjects Penjaskes sub Volleyball in SD N 06 Batang Gasan. Learning outcomes of students from the first cycle to the second cycle. The results of students in the first cycle was 57 (enough) increased to 83 (excellent) with an increase of 26%.